2010
DOI: 10.1007/s11664-010-1157-9
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Diffusion Study in HgCdTe for Low p-Type Doping in Auger-Suppressed Photodiodes

Abstract: Controllable p-type doping at low concentrations is desired for multilayer HgCdTe samples in a P + /p/N + structure due to the promise of suppressing Auger processes, and ultimately reduced dark current for infrared detectors operating at a given temperature. In this study, a series of arsenic implantation and annealing experiments have been conducted to study diffusion at low Hg partial pressure with the goal of achieving effective control over dopant profiles at low concentration. Arsenic dopant profiles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The (111)B HgCdTe epitaxial layer was grown in a horizontal, near-a pressure Aixtron AIX-200 MOCVD system on a 2-inch (100) GaAs substrate We note that there are extensive experimental and theoretical analyses in the literature of the extraction and exclusion phenomenon [7][8][9][10][11][12][13]. Here, we focus on analyzing these two effects separately based on experimental and theoretical results for an LWIR HgCdTe photodiode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The (111)B HgCdTe epitaxial layer was grown in a horizontal, near-a pressure Aixtron AIX-200 MOCVD system on a 2-inch (100) GaAs substrate We note that there are extensive experimental and theoretical analyses in the literature of the extraction and exclusion phenomenon [7][8][9][10][11][12][13]. Here, we focus on analyzing these two effects separately based on experimental and theoretical results for an LWIR HgCdTe photodiode.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence of the decrease in electron co (n) to almost zero, the hole concentration (p) decreases to the acceptor doping leading to a reduction in the Auger generation rate, and consequently dark c factor of 2ni/NA, where ni is the intrinsic carrier concentration, with an impr detectivity by (2ni/NA) 1/2 [6]. We note that there are extensive experimental and theoretical analyses i ture of the extraction and exclusion phenomenon [7][8][9][10][11][12][13]. Here, we focus o these two effects separately based on experimental and theoretical results f HgCdTe photodiode.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several literature studies have been published on the issues surrounding Auger-suppressed HgCdTe photodiodes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Among other things, the numerical modeling of predicted parameters [ 10 , 11 ], engineering steps (aimed at optimizing the photodiode architecture [ 12 ] and noise [ 13 ]), and time response studies (which have shown that the highest detectivity is obtained close to the negative resistance conditions at the expense of a long time constant [ 14 , 15 , 16 ]) were performed.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason MOCVD growth seems to be more attractive because it allows obtaining in situ both donor and acceptor doping [16,17]. However, low p-type doping levels in the absorber region usually require metal vacancies annihilation using two-zone annealing in sealed quartz ampoules at temperatures over 300 • C after growth process in both MBE [18] and MOCVD [19,20] systems. Recently, improved performance of HgCdTe uncooled photodiodes grown by MOCVD without post growth annealing procedure has been reported in [21].…”
Section: Introductionmentioning
confidence: 99%